Mitochondrial quality control in hematopoietic stem cells: mechanisms, implications, and therapeutic opportunities - Yun Liao; Stacia Octaviani; Zhen Tian; Samuel R. Wang; Chunlan Huang; Jian Huang (Stem Cell Research & Therapy)
Abstract Mitochondrial quality control (MQC) is a critical mechanism for maintaining mitochondrial function and cellular metabolic homeostasis, playing an essential role in the self-renewal, differentiation, and long-term stability of hematopoietic stem cells (HSCs). Recent research highlights the central importance of MQC in HSC biology, particularly the roles of mitophagy, mitochondrial biogenesis, fission, fusion and mitochondrial transfer in regulating HSC function. Mitophagy ensures the removal of damaged mitochondria, maintaining low levels of reactive oxygen species (ROS) in HSCs, thereby preventing premature aging and functional decline. Concurrently, mitochondrial biogenesis adjusts key metabolic regulators such as mitochondrial transcription factor A (TFAM) and peroxisome proliferator-activated receptor-γ coactivator 1α (PGC-1α) to meet environmental demands, ensuring the metabolic needs of HSCs are met. Additionally, mitochondrial transfer, as an essential form of intercellular material exchange, facilitates the transfer of functional mitochondria from bone marrow stromal cells to HSCs, contributing to damage repair and metabolic support. Although existing studies have revealed the significance of MQC in maintaining HSC function, the precise molecular mechanisms and interactions among different regulatory pathways remain to be fully elucidated. Furthermore, the potential role of MQC dysfunction in hematopoietic disorders, including its involvement in disease progression and therapeutic resistance, is not yet fully understood. This review discusses the molecular mechanisms of MQC in HSCs, its functions under physiological and pathological conditions, and its potential therapeutic applications. By summarizing the current progress in this field, we aim to provide insights for further research and the development of innovative treatment strategies.